2015
DOI: 10.1093/pm/pnv067
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Intradiscal, Intrathecal, and Intravascular Flow During the Performance of Retrodiscal (Infraneural) Approach for Lumbar Transforaminal Epidural Steroid Injections

Abstract: This retrospective review demonstrates that a relatively high rate of inadvertent intradiscal injections occurs in the performance of the retrodiscal approach for TFESI. This has significant implications in terms of the potential risk of disc injury induced by the needle puncture. The high incidence of intrathecal injections may also be of great concern depending upon the injectate delivered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 20 publications
0
25
1
Order By: Relevance
“…A number of concerns have been raised regarding the side effects of TFEI such as lower-limb paraplegia resulting from intravascular penetration or embolic infarct (41). The incidence of pain or discomfort related to nerve root damage and intradiscal penetrations was also higher in TFEI than in ILEI, probably because of the needle approach (4,18,42). Taken together, ILEI could be a suitable alternative to TFEI or the first choice of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…A number of concerns have been raised regarding the side effects of TFEI such as lower-limb paraplegia resulting from intravascular penetration or embolic infarct (41). The incidence of pain or discomfort related to nerve root damage and intradiscal penetrations was also higher in TFEI than in ILEI, probably because of the needle approach (4,18,42). Taken together, ILEI could be a suitable alternative to TFEI or the first choice of treatment.…”
Section: Discussionmentioning
confidence: 92%
“…To avoid intra‐arterial injection some schools recommend approaching the inferior part of the neuroforamen (especially for injections above L3), as the artery of Adamkiewicz rarely traverses this part of the foramen The approach is therefore in accordance with the Kambin triangle (Figure ) and is also referred to as the retrodiscal technique. As the endpoint is located immediately posterior of the disc, it provides a higher chance for accidental disc punctures . It is also unclear to which extent a correct epidural contrast flow can be achieved with this approach.…”
Section: Which Route For Administering Epidural Corticoids?mentioning
confidence: 99%
“…As the endpoint is located immediately posterior of the disc, it provides a higher chance for accidental disc punctures. 176 It is also unclear to which extent a correct epidural contrast flow can be achieved with this approach.…”
Section: Conclusion Of the Work Groupmentioning
confidence: 99%
“…Using the RD approach, the needle tip may unintentionally be placed too far ventrally and enter the IVD. Levi et al (38) performed 257 RD TF injections, and demonstrated a 4.7% rate of intradiscal injection. Needle entry into the IVD may be of concern for several reasons.…”
Section: Discussionmentioning
confidence: 99%